Pediatric Radiation Oncology in the Era of COVID‐19: A Single Institution Analysis - Melisa Pasli; Michael C. Larkins; George Edwards; Megan Goins; Dayana Gonzalez; Cathleen Cook; Andrew W. Ju; Aidan Burke (Cancer Reports, 2025)
ABSTRACT Aims As a result of the COVID‐19 pandemic, health inequities have garnered heightened attention in the public consciousness. In particular, rural access to diagnosis and radiotherapy (RT) for pediatric oncology patients was markedly affected during this period. The fractionated nature of RT creates a transportation burden for this population. We reviewed our institutional experience with pediatric oncologic therapy at a tertiary academic center serving a primarily rural population over a large geographic area. Methods Pediatric patients aged ≤ 18 years diagnosed with cancer between 2018 and 2022 at our institution were investigated, and we identified the subset of patients who received RT at our institution. Patients were categorized as pre‐COVID onset (diagnosed between 2018 and January 31, 2020) or post‐COVID onset (diagnosed on or after January 31, 2020, to December 1st, 2022). Chi‐Square and Student's t‐tests were used to elucidate associations between patient demographics and treatment modalities in the pre‐ and post‐COVID onset groups. Results A total of 114 patients were identified. For patients that received RT (n = 22), 4.5 times more patients traveled from rural counties post‐COVID onset (p = 0.027). These patients also saw increased rates of central nervous system (CNS) and non‐hematologic cancer diagnosis (p = 0.013 and 0.049, respectively). No difference was seen concerning race, patient age, or average distance traveled (p = 0.371, 0.249, and 0.420, respectively). No difference was seen in the estimated transportation cost incurred as a result of RT treatment (p = 0.144) or in treatment with concurrent chemotherapy (p = 0.245). For the entire cohort, no associations were seen concerning age, race, rural versus urban home county, cancer primary site, or in the prevalence of hematologic‐ or CNS‐based cancers. Conclusion Our results highlight the importance of understanding barriers to care to improve outcomes in rural pediatric patients, as the burden of RT may be greater for these patients than for those living in urban counties. Further investigation into barriers to treatment among rural pediatric patients undergoing RT is warranted.